A typical Brillouin light scattering spectrum in the SrLaALO4 (SLAO) crystal - Błachowicz, T.; Kleszczewski, Z. (Archives of Acoustics, 2002)
A new wide-band frequency component in the Brillouin spectrum, arising from absorption, has been detected in the SLAO oxide crystal. This completes the typical Brillouin spectrum, where Rayleigh lines, inelastic Stokes and anti-Stokes lines have been observed as a result of scattering from bulk acoustic phonons and, for some experimental configurations, on surface acoustic phonons. This newly discovered spectral component is distributed uniformly in frequency, independently of the light power incident on a sample, and depends on the incident wavelength.